Diversity of Bird in Cultivated Area Kamojang Crater, Laksana Tourism Village, Ibun-Bandung - Rasiska, Siska; Asdak, Chay; Parikesit, Parikesit; Sudarjat, Sudarjat; Gunawan, Budhi; Setiawan, Iwan (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2025)
The birds have an important role in the cultivated areas Kamojang Crater, Cikaro subwatershed, Laksana Tourism Village, Ibun - Bandung District. The study aims to explore the diversity of birds and classified them in guild groups. The census method was carried out in June-November 2022, with a sample point count technique with a radius of 50 meters and a distance between the center point of at least 200 meters, observed in the morning (06.00-10.00 am) and afternoon (14.00-16.00 pm) at each point for 10 minutes. Located in cultivated areas were near the nature reserve (NR), nature tourist park (NTP),protected forest (PF), and agricultural land (AL). The results showed that the birds are found 270 individu , 21 species, 7 ordo, dan 18 family. In general, the diversity of bird species in the Kamojang Crater cultivated area tends to be moderate (2,53), with a high abundance (4,09), birds species are equal in each location (0.80) and none dominate (0,11). The birds have higher Important Value Index in NR, NTP is Prinia familiaris (73,16 dan 53,58), in PF Lonchura leucogastroides (47,63), and AL is Apus Affinis (79,87). Birds found in cultivated areas near NR, NTP and AL are dominated by insectivore birds, while in the cultivated area near PF are predominated by granivore birds. According to the Similarity Index, bird communities in cultivated areas near NR have strong similarities with birds communities near NTP (62.5%, 76.92%, 29.71% and 63.06%).